Historical linguistics 2022: selected papers from the 25th International Conference on Historical Linguistics, Oxford, 1-5 August 2022 - Kennard, Holly; Lindsay-Smith, Emily; Lahiri, Aditi; Maiden, Martin (Amsterdam studies in the theory and history of linguistic science, 2025)
"This book offers a peer-reviewed selection of the best and most original contributions to the twenty-fifth International Conference on Historical Linguistics. They faithfully reflect the spirit of the Conference in that they all display a shared passion for the diachronic study of language but also an exciting diversity of research questions, theoretical approaches, linguistic phenomena, and languages explored. Data are drawn from Algonquian, Arandic, Bantu, Cushitic, Edoid, Indo-European, Manchu, Tangkic, Tungusic, and Uralic-among other languages and language-families. In addition to addressing, always with new insights, more traditional concerns of historical linguistics, such as reconstruction, classification, the effects of contact and borrowing, the determinants of morphological, syntactic, phonological, and semantic change, this book presents studies on less conventional topics, for example the diachrony of ideophones"